Root-Knot and Cyst Nematodes Activate Procambium-Associated Genes in Arabidopsis Roots - Yamaguchi, Yasuka L.; Suzuki, Reira; Cabrera, Javier; Nakagami, Satoru; Sagara, Tomomi; Ejima, Chika; Sano, Ryosuke; Aoki, Yuichi; Olmo, Rocio; Kurata, Tetsuya; Obayashi, Takeshi; Demura, Taku; et al. (Frontiers in Plant Science, 2017)
Developmental plasticity is one of the most striking features of plant morphogenesis, as plants are able to vary their shapes in response to environmental cues. Biotic or abiotic stimuli often promote organogenesis events in plants not observed under normal growth conditions. Root-knot nematodes (RKNs) are known to parasitize multiple species of rooting plants and to induce characteristic tissue expansion called galls or root-knots on the roots of their hosts by perturbing the plant cellular machinery. Galls contain giant cells (GCs) and neighboring cells (NCs), and the GCs are a source of nutrients for the parasitizing nematode. Highly active cell proliferation was observed in galls. However, the underlying mechanisms that regulate the symptoms triggered by the plant-nematode interaction have not yet been elucidated. In this study, we deciphered the molecular mechanism of gall formation with an in vitro infection assay system using RKN Meloidogyne incognita, and the model plant Arabidopsis thaliana. By taking advantages of this system, we performed next-generation sequencing (NGS)-based transcriptome profiling, and found that the expression of procambium identity-associated genes were enriched during gall formation. Clustering analyses with artificial xylogenic systems, together with the results of expression analyses of the candidate genes, showed a significant correlation between the induction of gall cells and procambium-associated cells. Furthermore, the promoters of several procambial marker genes such as ATHB8, TDR and WOX4 were activated not only in M. incognita-induced galls, but similarly in M. javanica induced-galls and Heterodera schachtii-induced syncytia. Our findings suggest that phytoparasitic nematodes modulate the host’s developmental regulation of the vascular stem cells during gall formation.